Misunderstanding on fasting practice in Rajab / Mohd Farhan Md Ariffin and Khadher Ahmad - Ahmad, Mohd Farhan Aliff; Ahmad, Khadher (Universiti Teknologi MARA, Perlis, 2016)
In the phase of approaching Ramadan, arise many questions on religious worship in two previous months every year. Among key practices that are often debated is fasting in Rajab. Most obvious, the dispute involving “believers” that constantly defending their standpoint and group respectively. On the other hand, they announce ostensibly so-called Rajab has many blessings, and sometimes the preferential advantages seen exceed Ramadan. On the other hand, they are strictly prohibits and as a result giving rise towards tabdi’ and tafsiq culture. Therefore, an effort to harmonize both parties seem important to express moderate views. Based on the analysis of qualitative methods, researcher strive to highlight real understanding in this matter. The study focuses specifically on the discussion regarding Rajab hadith status, have found many fake hadith regarding the invalidity of fasting specifically in Rajab. As a result, it was found that fasting in Rajab in particular is not accurate. However it can be carried out in general with full understanding to its implementation reason. It is hoped this article is beneficial to help unravel ummah problem and clarify current situation.